2000
DOI: 10.1029/1999rs002247
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of radioholographic methods of processing radio occultation data

Abstract: Abstract.Two methods for the determination of refraction angle profiles from radio occultation measurements in nmltipath areas are analyzed and compared: (1) the radio-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 17 publications
1
53
0
Order By: Relevance
“…Refractivity pro files are re trieved from GPS RO sig nals re ceived by the COS MIC sat el lites us ing the pro cess ing pro ce dures ex plained in de tail by Kuo et al (2004). The CDAAC data pro cess ing soft ware in cludes four radioholographic al go rithms, that is, back prop a ga tion met hod (Gorbunov et al 2000), slid ing spec tral method (Sokolovskiy 2001a), ca non i cal trans form method (Gorbunov 2002), and full spec trum in ver sion (FSI) method (Jensen et al 2003) in or der to in vert RO sig nals which passed through the moist tro po sphere where the multipath prop a ga tion is com mon and the con ven tional (geo met ric op tics) method does not work. The COS MIC refractivity pro files in the lower tro po sphere are de rived by the FSI method since it is op ti mal as to ac cu racy and com pu ta tional cost.…”
Section: Data and Methods Of Com Par I Sonsmentioning
confidence: 99%
“…Refractivity pro files are re trieved from GPS RO sig nals re ceived by the COS MIC sat el lites us ing the pro cess ing pro ce dures ex plained in de tail by Kuo et al (2004). The CDAAC data pro cess ing soft ware in cludes four radioholographic al go rithms, that is, back prop a ga tion met hod (Gorbunov et al 2000), slid ing spec tral method (Sokolovskiy 2001a), ca non i cal trans form method (Gorbunov 2002), and full spec trum in ver sion (FSI) method (Jensen et al 2003) in or der to in vert RO sig nals which passed through the moist tro po sphere where the multipath prop a ga tion is com mon and the con ven tional (geo met ric op tics) method does not work. The COS MIC refractivity pro files in the lower tro po sphere are de rived by the FSI method since it is op ti mal as to ac cu racy and com pu ta tional cost.…”
Section: Data and Methods Of Com Par I Sonsmentioning
confidence: 99%
“…Moreover, because BP does not take into account of the atmosphere, rays that diverge at the LEO could very well converge at the BP orbit if we were to position it too far back. To avoid intersection with these so-called imaginary caustics, Gorbunov et al [9] suggested a simple rule of thumb for the limb distance of the BP plane as x BP = R E α max , where R E is the radius of curvature of the Earth and α max is the maximum bending angle. For typical occultation parameters, x BP = 200 km.…”
Section: Formulationmentioning
confidence: 99%
“…In recent years, a number of "radioholographic" methods have been proposed that not only aimed to resolve the multipath problem encountered by the standard method but also to improve the vertical resolution of the retrievals [7,8,9,10,11,12]. These methods use both the amplitude and phase of the received signal in reconstructing the ray structure of the refracted field.…”
Section: Introductionmentioning
confidence: 99%
“…Using knowledge on the expected atmosphere conditions (included in the phase function ψ m (t)) for optimal measuring angular position of the ray's in angular spectrum is a main point of the radio holographic method. This is a main distinction from quantum cell approach now under elaboration by Gorbunov et al (2000). Spectral radio holographic method reveals only the rays in the angular spectrum that are in coherence (or matched in the sense of high resolution radar imaging technology) with the reference beam.…”
Section: Radio Holographic Methodsmentioning
confidence: 99%